Cerebral Cortex Involvement in Neuromyelitis Optica Spectrum Disorder - Kim, Woojun (J Clin Neurol, 2016)
BACKGROUND AND PURPOSE: Brain lesions involving the cerebral cortex are rarely described in patients with neuromyelitis optica spectrum disorder (NMOSD), in contrast to multiple sclerosis. We investigated cerebral cortex involvement using conventional brain magnetic resonance imaging (MRI) in anti-aquaporin-4 (AQP4)-antibody-positive NMOSD patients. METHODS: The study enrolled 215 NMOSD patients who were seropositive for the anti-AQP4 antibody from 5 referral hospitals, and retrospectively analyzed their demographic, clinical, and MRI findings. Abnormal cerebral cortex lesions on brain MRI were identified by a neuroradiologist and two neurologists using consensus. RESULTS: Most of the 215 enrolled patients (87%) were female. The median age at onset was 22.5 years (range: 15–36 years) and the mean follow-up duration was 123 months. Brain lesions were found in 143 of 194 patients (74%) in whom MRI was performed during follow-up. Brain lesions involving the cerebral cortex were identified in 6 of these 194 patients (3.1%). Five of the patients were female, and the six patients together had a median age of 29 years (range: 15–36 years) at the time of lesion presentation. Three of them showed leptomeningeal enhancement in the lesions. At presentation of the cortex-involving lesions, five of these patients were not being treated at the time of presentation, while the sixth was being treated with interferon-beta. CONCLUSIONS: Although rare, cortical involvement occurs in NMOSD and is commonly combined with leptomeningeal enhancement. We speculate that this occurs only in patients who are not treated appropriately with immunosuppressant drugs.